Our first experience with SPECT – CT Image Fusion - Gorczewski, Kamil; Steinhof, Katarzyna; Borys, Damian; Psiuk, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2004)
Computer tomography visualizes anatomical structures and abnormalities, but it lacks functional information. On the other hand, single photon emission tomography provides the missing information about the tumor function, but it has relative low resolution and the localization of the visible focus may be difficult, especially when iodine 131 I is used. Thus, several methods of image fusion are applied. We present an algorithm of image fusion based on affine transformation. On the basis of a phantom study, we showed that the created program can be a useful tool to fuse CT and SPECT images and then we applied it to patients’ data sets. Am external marker method was used to align patient’s functional and anatomical data. Image alignment quality depends on appropriate marker placement and acquisition protocol. The program estimates maximal misalignment in a volume between the markers. Created acquisition protocol minimizes misalignment of patient placement on both CT and gamma camera, however misalignment derived from respiratory movements cannot be avoided. The proposed technique is simple, low-cost and can be easily adopted in any hospital or diagnostic center equipped with a gamma camera and CT. The results obtained in the first 4 patients are also shown and discussed. Fusion of morphology and function can improve diagnostic accuracy in many clinical circumstances.